Boundary Behavior of General Kobayashi Metrics on h-Extendible Domains - Thu, Ninh Van; Huyen, Do Khanh; Kim Son, Nguyen Thi (VNU Journal of Science: Mathematics - Physics; Vol 40 No 3DO - 10.25073/2588-1124/vnumap.4948, 2024)
The purpose of this article is to prove the existence of -nontangential limits of the general Kobayashi metrics at -extendible boundary point. This is a generalization of Yu’s result for -nontangential limits .